2020
DOI: 10.1007/978-3-030-45688-7_51
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Consumer Behavioural Intention to Accept Technology: Towards Autonomous Vehicles Technology Acceptance Model (AVTAM)

Abstract: The work presented in the paper aims at exploring information technology acceptance in the context of Autonomous Vehicles (AV) with the objectives of identifying and testing the constructs that will influence future AVs acceptance. Most models of technology acceptance focus on barriers of successful information technology implementation in organisations and technologies that have already been deployed. There is only a small number of studies conducted on emerging and disruptive technologies such as AV. We addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…(1985). Many researchers found that behavioural intentions have a significant influence on the user adoption intention of a new technology (Seuwou P et al (2020), Jin-Soo Lee et al ( 2010), (Patel, 2021). In this paper behavioural intention refers to how a person feels to having a crypto in his portfolio.…”
Section: E Behavioural Intentionsmentioning
confidence: 97%
“…(1985). Many researchers found that behavioural intentions have a significant influence on the user adoption intention of a new technology (Seuwou P et al (2020), Jin-Soo Lee et al ( 2010), (Patel, 2021). In this paper behavioural intention refers to how a person feels to having a crypto in his portfolio.…”
Section: E Behavioural Intentionsmentioning
confidence: 97%
“…Support refers to "the degree of support provided by the organization and policy environment for the digital adoption". Previous research has shown that support from the organization, government, and legislation can positively impact employees' perceived usefulness and perceived ease of use of digital technology [73,74]. Furthermore, support plays a crucial role in determining users' intention to use technology [75].…”
Section: Internal Factorsmentioning
confidence: 99%
“…Now those rules may begin to change [31]. In this scenario, it is difficult to identify who to blame [38]. Is it the car owner, or the AV manufacturer?…”
Section: Legal Implicationsmentioning
confidence: 99%
“…These AVs also learn from their mistakes and improve their accuracy faster than any probable human driver. Today, it is recognised that more than 50% of innovations in vehicles are on electronic components [38]. Most cars are now equipped with some level of automation to assist drivers when parking their vehicles or following other vehicles.…”
Section: Introductionmentioning
confidence: 99%